2020
DOI: 10.36740/wlek202001124
|View full text |Cite
|
Sign up to set email alerts
|

Time Course of Endothelial Dysfunction and Atherothrombosis Markers in Patients With Acute Myocardial Infarction With St Segment Elevation and Type 2 Diabetes Mellitus Depending on Reperfusion Therapy Approach

Abstract: The aim: To evaluate the levels of plasminogen activator type 1 inhibitor, asymmetric dimethylarginine and endothelial nitric oxide synthase on day 10-14 in patients, depending on the presence or absence of concomitant type 2 diabetes and the type of reperfusion therapy. Materials and methods: The study involved 130 patients with acute myocardial infarction, divided into 2 groups: Group 1 consisted of patients with acute myocardial infarction with type 2 diabetes mellitus (n = 73), Group 2 comprised patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Our results related to NOS levels in diabetic patients with acute coronary occlusion were supported in the scientific research of Minukhina D. and co-authors, which showed considerable reduction of NOS levels in patients with AMI and concomitant type 2 DM. Performing of percutaneous coronary intervention did not contribute to the statistically significant increasing of NOS [18] compared to non-invasive therapy in diabetic patients. This trend is apparently due to the additional negative impact of metabolic disorders associated with type 2 DM on the endothelium of the coronary arteries, accompanied by increased release of sCD40L and PAI-1, which cause the development of intravascular inflammation in the arterial wall, inhibition of fibrinolysis of the formed thrombus, as well as reducing the synthesis of endothelial NOS, which is responsible for the regulation of vascular tone.…”
Section: Resultsmentioning
confidence: 67%
“…Our results related to NOS levels in diabetic patients with acute coronary occlusion were supported in the scientific research of Minukhina D. and co-authors, which showed considerable reduction of NOS levels in patients with AMI and concomitant type 2 DM. Performing of percutaneous coronary intervention did not contribute to the statistically significant increasing of NOS [18] compared to non-invasive therapy in diabetic patients. This trend is apparently due to the additional negative impact of metabolic disorders associated with type 2 DM on the endothelium of the coronary arteries, accompanied by increased release of sCD40L and PAI-1, which cause the development of intravascular inflammation in the arterial wall, inhibition of fibrinolysis of the formed thrombus, as well as reducing the synthesis of endothelial NOS, which is responsible for the regulation of vascular tone.…”
Section: Resultsmentioning
confidence: 67%
“…However, with the continuous development of contemporary medical technologies and constant improvement in diagnostic and therapeutic means for AMI, the mortality rate of the disease has been reduced remarkably through multiple medico-surgical management measures, including new drugs and percutaneous coronary intervention (PCI). Research evidence indicates that atrial fibrillation often occurs in AMI patients after PCI, which is a primary factor influencing the effective rate of treatment and postoperative quality of life of such patients [4] [5] . However, currently, there are no definite peripheral blood indexes for evaluating the severity of AMI, the cardiovascular risk factors, and the incidence rate of atrial fibrillation after PCI.…”
Section: Introductionmentioning
confidence: 99%